Green economy or green society? Contestation and policies for a fair transition - Cook, Sarah; Smith, Kiah; Utting, Peter (Geneva, 2012)
"Based on research from the UNRISD inquiry into the social dimensions of green economy, this paper outlines a conceptual and policy approach to bring social concerns more centrally into green economy and sustainable development debates."